The Philosophy of Equality - Paul A. Freund (Washington University Law Quarterly, 1979)
Inequality derives not merely from a division of labor or functions, but from the establishment of norms and corresponding evaluations of persons.
Keywords: Jurisprudence; Equality; Philosophy